Перспективні матеріали для фільтраційних мембран харчової промисловості - Пащенко, Богдан Сергійович; Литвиненко, Олександр Анатолійович; Штефан, Євгеній Васильович (Київ: НУХТ, 2016)
У статті наведено результати експериментальних досліджень зносостійкості керамічних матеріалів для виготовлення мембран для харчової та переробної промисловості. Проведено експерименти з визначення механічної стійкості перспективних конструкційних матеріалів для виготовлення мембранних фільтрувальних елементів. Встановлено, що високі міцністні характеристикизабезпечують динамічну стійкість мембран і тривалий термін їх експлуатації.

The results of experimental research of the wear resistance of ceramic materials for the manufacture of membranes for food and processing industry are present in the article. The authors are considered advantages of ceramic elements in comparing with polymer and also methods of their manufacturing. Experiments for determining of the mechanical stability of the perspective construction materials for the manufacture of the membrane filter elements are conducted. High strength indicators of the technical ceramics which are depending on the content of the base component are proven, especially materials based on aluminum oxide for the manufacturing the membrane filter elements, which providing conditions hygienic design of the technological equipment. It is found that the high strength characteristics are providing a dynamic stability of membrane and long term of their exploitation
Keywords: фільтраційні мембранні елементи; керамічні матеріали; зносостійкість; the filter membrane elements; ceramic materials; durability; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра експертизи харчових продуктів